Simultaneous Estimation of Ombitasvir, Paritaprevir and Ritonavir in Tablet Dosage Form by Reverse Phase High-Performance Liquid Chromatography: Pharmaceutical Science-Pharmaceutical Analysis - Nagaraju, Gollapalli; Agarwal, Ritesh; Nadendla, Rama Rao (International Journal of Life Science and Pharma Research, 2022)
Ombitasvir/paritaprevir/ritonavir are the newest medicines approved for use in the treatment of hepatitis C virus (HCV) and are available in tablet form as an oral combination. Specifically, these agents are indicated in the treatment of HCV in patients with genotype 1 infection. Due to the therapeutic importance and increased use of Viekira Pak, proper methods for its determination in bulk and pharmaceutical formulations must be developed. The purpose of this work is to develop an accurate and precise RP-HPLC method for the determination of ombitasvir, paritaprevir and ritonavir in bulk and pharmaceutical preparations. Drugs were separated using Inertsil ODS-C18; 5μm (4.6 X 250mm) column using a mobile phase consisting of 0.02M phosphate buffer (pH-4.5): Acetonitrile: Methanol, (50:30:20) (v/v). The retention time was 2.98, 3.77 and 4.70 min for Ombitasvir, Paritaprevir, Ritonavirrespectively and total run time was 10 min. at a flow rate of 1.0 mL/ min and the detection wavelength was 262 nm. The linearity was observed in the range of 15-45μg/ mL for ombitasvir, paritaprevir and ritonavir with a correlation coefficient of 0.9903, 0.9996 and 0.9998 respectively. The proposed method was validated for its linearity, accuracy, precision and robustness. This method can be employed for routine quality control analysis of Ombitasvir, Paritaprevir and Ritonavir in tablets. The LOD and LOQ values were found to be 1.8, 0.29 and 0.69 μg/ mL and 5.7, 0.90 and 2.10 μg/ mL for Ombitasvir, Paritaprevir and Ritonavir, respectively. The proposed method was successfully applied for the determination of ombitasvir/paritaprevir/ritonavir tablets, without interference from the excipient peaks. Hence, the method can be applied for the routine quality control analysis of the studied drugs, either in bulk or dosed forms.